CLUSTER STRUCTURES IN DEVELOPMENT EMPLOYMENT OF RURAL TERRITORY OF THE REGION - UZHVA, Alla; LITVINOV, Dmytro (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article outlines the current state of socio-economic development of the region in the direction of the social sphere. It was established that the current state of the socio-economic infrastructure of the village confirms the presence of a deep crisis. The difficult situation of the village economy, long-term underfunding of the social sphere led to the threat of physical destruction of its material and technical potential. The existing material base of cultural and household facilities does not meet the standards. In rural areas, educational facilities in most cases do not have modern technical equipment for teaching, there is a shortage of teaching staff, and the level of their professional education is lower than in the city. The problems of employment in the rural areas of the region are analyzed. It was found that the employed population, which is released from agriculture for various reasons, can engage in non-agricultural activities, which will positively affect the growth of the income of the rural population. Therefore, it is possible to use not only agricultural land, but also natural and recreational resources, as well as a favorable habitat. However, local authorities do not pay due attention to the development of agricultural activities in the countryside, livestock farms and agricultural processing enterprises are shrinking. It is proposed to form an agricultural-tourist cluster to ensure uninterrupted supply of ecologically clean agricultural products and to solve the issue of employment of the region’s population. Thus, as an example of such formation, the agricultural and touristic potential of the Berezan district was used, within which there are 4 recreation areas: "Koblevo", "Lugove", "Morske", "Rybakivka". About 170 recreation centers offer their services to tourists from Ukraine and near abroad. About 180,000 people visit the Koblevo-Rybakiv recreation area every year. In order to provide 180,000 tourists with environmentally friendly food during the 5 months of the holiday season, it is necessary to allocate 6.4 hectares of arable land for the production of leafy vegetables, early cabbage, early potatoes, seasonal vegetables, melons and sweet corn; 28.6 hectares of perennial plantations for the production of berries and grapes; 856 hectares of agricultural land for the production of food products of animal origin. For the production of fresh baked goods, the peasants must purchase high-quality flour of industrial production. When forming the production zone, it is necessary to take into account the need to minimize transport costs. It was emphasized that the cluster should include rural areas located along the M14 highway and no further than 20-25 km from the Koblevo-Rybakiv recreation area. These are rural settlements that are under the jurisdiction of the Koblev Rural United Territorial Community. The number of able-bodied population within its borders is 5,514 people.